Statutory and operative definitions of legal terms in the tax law - Artur Halasz (Prawo Budżetowe Państwa i Samorządu, 2019)
In this paper the author discusses the question of defining legal terms in the tax law. The author divides the definitions of legal terms contained in the tax law into statutory and operative definitions. This division is based on the distinction between statutory and operative law. Moreover, the author points to the operative definitions of legal terms in the tax law, which are of a quasi-statutory nature.